The Relationship Between Individual Factors and Critical Thinking: A Multidimensional Approach - DÁVID, Tamás; BOTH, Sándor-Ágoston; BARTA, Andrea (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
Critical thinking has received increasing attention in recent years with the aim of eliminating the shortcomings of traditional education. Numerous interventions and programmes have been created to develop this skill, which is a significant factor in students' educability, academic performance. In spite of the rising attention, a much smaller proportion of research on critical thinking examines factors outside the classroom that nevertheless contribute significantly to critical thinking skills. The aim of our research is to examine critical thinking dispositions and the factors that influence them, with a particular focus on conformity, religious beliefs, impulsivity and negative life events. The research questions we formulated are as follows: Do conformity and impulsivity predict critical thinking dispositions? How do religious beliefs and negative life events predict critical thinking dispositions? The research strategy is quantitative, predictive research, and the target population is Hungarian-speaking psychology and special education students at Babeș-Bolyai University. A non-probability, quota sampling procedure was used. According to the results of the research, impulsivity (p < .001) and conformity (p < .001) predict lower critical thinking dispositions, while experiencing negative life (p < .001) events predict higher critical thinking dispositions. Religious beliefs (p = 0.309) did not show a significant correlation with critical thinking dispositions.